2016
DOI: 10.1002/jcb.25519
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Regulates High Mobility Group A2 Expression in Human Bone Marrow‐Derived Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are an excellent source for numerous cellular therapies due to their simple isolation, low immunogenicity, multipotent differentiation potential and regenerative secretion profile. However, over-expanded MSCs show decreased therapeutic efficacy. This shortcoming may be circumvented by identifying methods that promote self-renewal of MSCs in culture. HMGA2 is a DNA-binding protein that regulates self-renewal in multiple types of stem cells through chromatin remodeling, but its impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The effect of miR-98-5p on the osteogenic differentiation of the mouse preosteoblast cell line, MC3T3-E1, was subsequently investigated in the current study. Consistent with previous studies (27,29), the results of the present study demonstrated that miR-98-5p significantly inhibited MC3T3-E1 cell osteogenic differentiation by repressing the expression of HMGA2. In addition, miR-98-5p upregulation significantly inhibited cell viability and induced apoptosis in MC3T3-E1 cells and these effects were eliminated by HMGA2 overexpression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The effect of miR-98-5p on the osteogenic differentiation of the mouse preosteoblast cell line, MC3T3-E1, was subsequently investigated in the current study. Consistent with previous studies (27,29), the results of the present study demonstrated that miR-98-5p significantly inhibited MC3T3-E1 cell osteogenic differentiation by repressing the expression of HMGA2. In addition, miR-98-5p upregulation significantly inhibited cell viability and induced apoptosis in MC3T3-E1 cells and these effects were eliminated by HMGA2 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…HMGA2 is a nuclear-binding protein that serves an important role in the regulation of cell proliferation and differentiation (26). A previous study has demonstrated that HMGA2 knockdown results in the inhibition of MSC proliferation (27). The effect of miR-98-5p on the osteogenic differentiation of the mouse preosteoblast cell line, MC3T3-E1, was subsequently investigated in the current study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several members of the HMGB family have been found to promote self-renewal and colony formation in stem cells as well as in cancer cells (22)(23)(24)(25)(26)(27)(28), indicating the presence of an association between these two cell types; however, the detailed molecular mechanisms underlying their cancer-promoting activity remain obscure. HMGB3 belongs to the HMGB family, members of which are proposed to regulate gene transcription by affecting DNA structure and influencing transcription complex formation or by altering gene availability (29).…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 exerts a positive effect in promoting chondrogenic differentiation when supplemented during cell expansion [17]. FGF2 inhibitory effect on adipogenesis has also been observed; this effect has been shown to involve the high mobility group A-2 (HMGA2) [18]. Additionally, FGF1 reduces the expression of BMP and activin membrane-bound inhibitor homolog (BAMBI) by affecting the PI3K pathway promoting adipogenic differentiation [19].…”
Section: Stem Cell Lineage Differentiation Towards Chondrogenesis or mentioning
confidence: 99%